The subject of cognition in the pedagogy of physical culture - Femiak, Joanna (Physical education, sport and olympism from a pedagogical perspective, 2023)
The article attempts to present the pedagogy of physical culture as the one that contributes to the creation of the vision of the subject of cognition, building its integrity thanks to corporeality.